Faith Leaders & the Outcome of the 2023 Presidential Election in Nigeria - Muhammad Maigari, Abdullahi (The Journal of Society and Media, 2024)
This study examines how the role of religion in a democratic environment is related to the history of democracy itself, especially in the country of Nigeria in 2023. Religious leaders often mobilize their congregations or allow politicians to use their podiums to mobilize support during elections. The findings of this study imply that religious leaders have now become active political actors in Nigeria, a country divided along ethnic and religious lines. The mobilization of voters based on ethnic and religious sentiments will have a negative impact on the development of democracy in the country, in the sense that leaders are chosen not based on the leadership qualities they possess or based on their competence, but rather based on primordial sentiments. This research uses explanatory research to explain and examine how religious leaders influence the results of several elections in Nigeria, especially the 2023 elections. This research uses secondary data from the Independent National Electoral Commission (INEC), an election management body in Nigeria